3D Printing of Lightweight for Lighter and Denser Parts - Sa'ude, Nasuha; Ibrahim, Mustaffa (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The lightweight nature of Polylactic acid is the new material that is being used in the additive manufacturing sector for the production of filament. This filament will produce wing components, which need particular features for the part to fly and be balanced with saves battery by reducing the material used. This study was conducted to determine the temperature at which it is best to print filaments produced from lightweight polylactic acid (LW-PLA) material to acquire optimal quality setting for components on the drone as well as something that can be installed and flown. The research findings have provided us with the knowledge that may be used to examine the outcomes of other studies and testing. Started with a dumbbell and cube preparation material that had 0 infills and was printed with four various types of temperatures. After that, we carried out tests broken down into three categories: thermal, mechanical, and physical testing. Various recommendations for changes are presented and discussed; among these recommendations is the proposal that the samples be managed and preserved. The part with a 200℃-printing setting has the largest mass, according to the results of the physical features, although it is still quite light. The mechanical testing results demonstrate that printing setting 200℃ is the greatest value needed to fracture the specimen. The experiment of physical, mechanical, and thermal qualities yielded 200 as the optimal temperature setting for the material (LW-PLA) print drone.